THE EMOTIONAL INTELLIGENCE OF LECTURERS WORKING IN THREE-PROVINCES IN SOUTHERN THAILAND THAT ARE EXPERIENCING SOCIAL AND POLITICAL UNREST - Praditsang, Mali (PEOPLE: International Journal of Social Sciences, 2018)
The main objective of the current study was to gauge the emotional intelligence level of the lecturers working in three-provinces in southern Thailand that are experiencing social and political unrest. To gauge this level, a survey comprising 75 questions was distributed to lecturers in Prince of Songkhla University, Yala Rajabhat University and Princess of Narathiwat University. The three-part questionnaire included questions about demographic factors, emotional intelligence and social intelligence. The subjects were 546 lecturers who worked in the University in Patani, Yala and Narathiwat provinces. The results of this study indicate that their emotional intelligence was uniformly high; lecturers from Yala Province has the highest level of emotional intelligence (mean=3.92) followed by lecturers from Patani (mean=3.76) and Narathiwat (mean=3.73). Among the possible reasons for these results were that these lecturers function well in the educational environment at the university, which is largely insulated from the general political climate and that they have learned to adapt to the vicissitudes of their daily life.